Development of a Flutter-Based Student Task Management Application Incorporating SQLite and Cubit State Management - Ival Arip Hamzah; Dani Ekaputra; Muhamad Lutfi Asihab (PT. ALRCA INOVASI DIGITAL, 2026)
The rapid advancement of mobile technology offers significant convenience in managing daily academic activities. Higher education students frequently encounter challenges when organizing coursework assignments originating from diverse modules with differing submission deadlines, often leading to submission delays and reduced academic productivity. To address these operational issues, a mobile task management application was developed using the Flutter framework, incorporating SQLite for offline persistent local database storage and Cubit for state management architecture. The application provides core functional capabilities consisting of Create, Read, Update, and Delete (CRUD) operations, accompanied by detailed task metadata including course title, deadline date, priority rating, and completion status. Because data is structured and stored locally on the client device, the software functions seamlessly without an active internet connection. System evaluation results demonstrate that the application operates stably on Android devices, all CRUD workflows execute accurately according to specification, and the Cubit state management pattern successfully preserves user interface consistency across dynamic state transitions